2008
DOI: 10.1111/j.1526-4610.2008.01175.x
|View full text |Cite
|
Sign up to set email alerts
|

Are Sleep Difficulties Associated With Migraine Attributable to Anxiety and Depression?

Abstract: Objective-To examine whether sleep complaints reported by migraineurs can be attributed to comorbid anxiety and/or depression.Background-A consistent association between migraine and sleep complaints has been reported in community and clinical studies. However, anxiety and depression are often comorbid with migraine. Thus, it may be possible that the increased prevalence of sleep problems in migraineurs is attributable to comorbid anxiety and depression. To our knowledge, no previous studies have demonstrated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
71
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(80 citation statements)
references
References 45 publications
7
71
0
2
Order By: Relevance
“…Both patients with migraine and tension type headache had higher daytime sleepiness as compared to controls. Vgontzas et al (2008) has found that the associations between sleep problems and migraine persisted even after controlling for lifetime and current anxiety and mood disorders [14].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Both patients with migraine and tension type headache had higher daytime sleepiness as compared to controls. Vgontzas et al (2008) has found that the associations between sleep problems and migraine persisted even after controlling for lifetime and current anxiety and mood disorders [14].…”
Section: Discussionmentioning
confidence: 98%
“…Sleep abnormalities detected among migraineurs were excessive daytime sleepiness, difficulty initiating and maintaining sleep, early morning awakening and daytime fatigue [3]. Vgontzas et al (2008) opined that the sleep disturbances in patients with migraine cannot be explained only by chance association or on the basis of co-morbid depression and anxiety [4]. There could be a biological basis to suggest a common pathway for regulation of sleep and pathogenesis of migraine.…”
Section: Introductionmentioning
confidence: 98%
“…In a cross sectional study, Boardman et al [20] identified a dose-response relationship between headache and sleep (eg, trouble falling or staying asleep, feeling tired or worn out): Among 2,662 respondents, headache frequency increased with the severity of sleep complaints, as the OR (adjusted for age and sex) was 2.4 (95% CI, 1.7-3.2) for mild complaints, 3.6 (95% CI, 2.6-5.0) for moderate complaints, and 7.5 (95% CI, 4.2-13.4) for severe sleep complaints. Controlling for anxiety and depression, Vgontzas et al [21] confirmed the association of sleep problems (trouble falling asleep, inadequate sleep) with migraine.…”
Section: Insomniamentioning
confidence: 92%
“…[52][53][54] Anxiety and depression may not entirely explain sleep disorders in adult migraineurs. 55 Several studies, the majority based on sleep questionnaires, including some that were population based, have drawn attention to the association between sleep disorders and childhood headache. [56][57][58][59][60][61][62] The association was stronger with migraine than TTH, although those with TTH (including CTTH) may not have been adequately represented.…”
Section: Disorders Of Sleepmentioning
confidence: 99%